Vedantha darsana & Acharya Vachaspathi Misra - Muttukrṣṇaśāstrī, Rā (Hithabhashini Publications, 1982)
Life and works of Vācaspatimiśra, fl. 976-1000, Hindu philosopher; with special reference to his contribution to the Advaita school.